Development and Practical Application of Character-Based Reading Materials in Junior High School English Instruction - Gusmaizal Syandri; Sirajul Munir; Julhadi Julhadi; Suyono Suyono (STAI Hubbulwathan Duri, 2025)
The integration of character values into English instruction is essential for holistic education, yet existing materials often emphasize linguistic skills over moral development. Teachers face challenges in promoting deeper internalization of values beyond the receiving and responding phases. This study addresses the gap by developing character-based English reading materials for junior high school students. The research employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) with a mixed-methods approach. Needs analysis was conducted through observations, interviews, and documentation, followed by product development. Practicality and effectiveness were evaluated using questionnaires, observation sheets, and pretest–posttest assessments involving two teachers and 28 students. The developed materials integrated key values such as integrity, responsibility, cooperation, diligence, and compassion into reading activities. Practicality tests showed very positive responses from teachers (M = 4.34) and students (M = 4.54). Student learning outcomes improved significantly, with scores increasing from a pretest average of 71.96 to a posttest average of 85.17. Classroom observations also confirmed high engagement, responsibility, and collaboration during lessons. The findings demonstrate that character-based reading materials enhance both language proficiency and moral development. The integration of reflective activities and value-based assessment supported students’ higher-order thinking and ethical reasoning, aligning with cognitive, affective, and social development theories. Character-integrated English reading materials are practical, effective, and align with curriculum goals. They bridge the scarcity of value-based instructional resources and provide a model for embedding character education in language learning. Future studies should examine long-term impacts and explore broader implementation across diverse educational contexts.